The System of Educology - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1999)
This article takes grounds for the classification of the branches of educational science. The author suggests the subject of educology to consider as a reliable ground for systematic classification. The article attempts to answer the doubts concerning the scientific status of education science. It is based on methods of comparative and systematic analysis.
Keywords: educology; system of educology; branches of educational science; object of educology